Pembelajaran Dalam Jaringan (Daring) Terhadap Hasil Belajar Siswa Pada Materi Larutan Elektrolit Dan Non Elektrolit Selama Masa Pandemi COVID-19 - Lauren Cornelia Agatha; Dokri Gumolung; Abdon Saiya (Chemistry Department, Universitas Negeri Manado, 2022)
The purpose of this study was to determine the magnitude of the effect of online learning on student learning outcomes in during the COVID-19 pandemic. This research was conducted in class X IPA SMA N 1 Tondano in the 2020/2021 academic year. A total of 25 students of class X IPA 1 were assigned as research samples. This study uses an experimental method with a One-Shot Case Study design. The results of this study consist of two data, namely questionnaire data for assessing student attitudes and post-test as an assessment of student learning outcomes which are then analyzed using correlation regression, and the regression equation obtained was Y = 9.5565 + 0.9073 x. The regression equation shows that the higher the student's attitude score (variable X), the higher the student's (variable Y). From the Product moment correlation test, it is found that the correlation coefficient (rxy) is 0.6599, which proves that the X and Y variables have a strong relationship. To calculate the effect of student attitudes on online learning on learning outcomes, it is calculated through the determinant coefficient formula, and it is found that the magnitude of the influence of student attitudes on online learning on learning outcomes is 43.55%. While the remaining 56.45% is influenced by other variables in the form of distractions and obstacles during online learning.